Distribution of Sb, As, Ge, and In between metal and silicate during accretion and core formation in the Earth. (1st February 2017) - Righter, K.; Nickodem, K.; Pando, K.; Danielson, L.; Boujibar, A.; Righter, M.; Lapen, T.J.
Abstract: A large number of siderophile (iron-loving) elements are also volatile, thus offering constraints on the origin of volatile elements in differentiated bodies such as Earth, Moon, Mars and Vesta. Metal–silicate partitioning data for many of these elements is lacking, making their overall mantle concentrations in these bodies difficult to model and origin difficult to distinguish between core formation and volatile depletion. To address this gap in understanding, we have undertaken systematic studies of four volatile siderophile elements – Sb, As, Ge and In – at variable temperature and variable Si content of metal. Several series were carried out at 1 GPa, and between 1500 and 1900 °C, for both C saturated and C-free conditions. The results show that temperature causes a decrease in the metal/silicate partition coefficient for all four elements. In addition, activity coefficients for each element have been determined and show a very strong dependence on Si content of Fe alloy. Si dissolved in metal significantly decreases the metal/silicate partition coefficients, at both 1600 and 1800 °C. The combination of temperature and Si content of the metal causes reduction of the metal–silicate partition coefficient to values that are close to those required for an origin of mantle As, Sb, Ge, and In concentrations by metal–silicate equilibrium processes. Combining these new results with previous studies on As, Sb, Ge, and In, allowed derivation of predictive expressions for metal/silicate partition coefficients for these elements which can then be applied to Earth. The expressions are applied to two scenarios for continuous accretion of Earth; specifically for constant and increasing fO2 during accretion. The results indicate that mantle concentrations of As, Sb, Ge, and In can be explained by metal–silicate equilibrium during an accretion scenario. The modeling is not especially sensitive to either scenario, although all element concentrations are explained better by a model with variable fO2 . The specific effect of Si is important and calculations that include only S and C (and no Si) cannot reproduce the mantle As, Sb, Ge, and In concentrations. The final core composition in the variable fO2 model is 10.2% Si, 2% S, and 1.1% C (or X Si  = 0.18, X S  = 0.03, and X C  = 0.04. These results suggest that core formation (involving a Si, S, and C-bearing metallic liquid) and accretion were the most important processes establishing many of Earth's mantle volatile elements (indigenous), while post-core formation addition or re-equilibration (exogenous) was of secondary or minor importance.